2013
DOI: 10.1021/pr4000448
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabotyping of Bladder Cancer Using Two-Dimensional Gas Chromatography Time-of-Flight Mass Spectrometry

Abstract: Cystoscopy is the gold standard clinical diagnosis of human bladder cancer (BC). As cystoscopy is expensive and invasive, it compromises patients' compliance toward surveillance screening and challenges the detection of recurrent BC. Therefore, the development of a noninvasive method for the diagnosis and surveillance of BC and the elucidation of BC progression become pertinent. In this study, urine samples from 38 BC patients and 61 non-BC controls were subjected to urinary metabotyping using two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 47 publications
5
86
0
Order By: Relevance
“…[138][139][140] In addition to GC/TOFMS, our laboratory applied GC×GC/TOFMS-based metabonomics in profiling BC. 59 The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The BC group could be clearly distinguished from the control groups with sensitivity and specificity of 91.3% and 92.5%, respectively. Their model also showed potential in differentiation between muscle-invasive and nonmuscle invasive BC.…”
Section: Metabotyping Of Bladder Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…[138][139][140] In addition to GC/TOFMS, our laboratory applied GC×GC/TOFMS-based metabonomics in profiling BC. 59 The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The BC group could be clearly distinguished from the control groups with sensitivity and specificity of 91.3% and 92.5%, respectively. Their model also showed potential in differentiation between muscle-invasive and nonmuscle invasive BC.…”
Section: Metabotyping Of Bladder Cancermentioning
confidence: 93%
“…56 Symptomatic controls should also be recruited to avoid confounding factors. 59 In BC metabonomic investigations, baseline characteristics such as stage and grade of tumor, hematuria (gross or micro), surgical interventions and smoking habit should be additionally taken into consideration during the study design. 60 …”
Section: Workflow In Bladder Cancer Metabonomicsmentioning
confidence: 99%
“…This study also enabled us to get some tips on the biological events that take place at the high and low-grade bladder tumor carcinogenesis. In another study Pasikanti et al [15] demonstrated down regulation of glycerol in patients with BC compared with non-BC control subjects (Table 1).…”
Section: Introductionmentioning
confidence: 91%
“…Various studies using mass spectrometric (MS) methods reported promising results for bladder cancer (BCa) detection and separation of invasive BCa from non-invasive BCa (Issaq et al, 2008;Huang et al, 2011;Pasikanti et al, 2013;Chan et al, 2015;Zhou et al, 2016). However, cohort sizes were small in most studies and the effects of renal cancer and bladder inflammation were the major problem in BCa detection (Van et al, 2011).…”
Section: Bladder Cancermentioning
confidence: 99%